2017
DOI: 10.4103/0366-6999.206359
|View full text |Cite
|
Sign up to set email alerts
|

Role of Diffusion-weighted and Contrast-enhanced Magnetic Resonance Imaging in Differentiating Activity of Ankylosing Spondylitis

Abstract: Background:Previous studies showed that combining apparent diffusion coefficient (ADC) value with the Spondyloarthritis Research Consortium of Canada (SPARCC) index value might provide a reliable evaluation of the activity of ankylosing spondylitis (AS), and that contrast-enhanced (CE) magnetic resonance imaging (MRI) is unnecessary. However, the results were based on confirming only a small random sample. This study aimed to assess the role of CE-MRI in differentiating the disease activity of AS by comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In the current study, it was found that in active AS, bone marrow edema and increased vascular permeability caused an enlarged extracellular space and increased water molecular diffusion . Zhao et al reported that the ADC and D values derived from DWI and IVIM were increased in active AS, findings that were consistent with our findings . Previous studies have also showed that DWI‐derived ADC and IVIM‐derived D values were increased with decreased bone mineral density in AS patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, it was found that in active AS, bone marrow edema and increased vascular permeability caused an enlarged extracellular space and increased water molecular diffusion . Zhao et al reported that the ADC and D values derived from DWI and IVIM were increased in active AS, findings that were consistent with our findings . Previous studies have also showed that DWI‐derived ADC and IVIM‐derived D values were increased with decreased bone mineral density in AS patients.…”
Section: Discussionsupporting
confidence: 91%
“…3,12 Zhao et al reported that the ADC and D values derived from DWI and IVIM were increased in active AS, findings that were consistent with our findings. 15,26 Previous studies have also showed that DWI-derived ADC and IVIM-derived D values were increased with decreased bone mineral density in AS patients. The correlation between the ADC or D value and bone mineral density in AS patients requires further confirmation.…”
Section: Discussionmentioning
confidence: 98%
“…However, Zhao et al . 113 confirmed these results by using a large sample of patients, showing that the combination of short tau inversion recovery (STIR) and diffusion weighted imaging (DWI) in MRI is sufficient to monitor disease activity, avoiding the unnecessary use of contrast with its risks. Conversely, Bradbury et al .…”
Section: Imagingmentioning
confidence: 62%
“…Regarding the SIJ MRI in the same cohort (SPACE), the use of an IV MRI contrast agent (gadolinium), which is essential for the detection of synovitis and/or capsulitis, failed to increase the sensitivity of the test compared with STIR alone, because these acute lesions were only observed in patients who also presented bone marrow edema (visible on STIR) [20] (2B). In addition, the acquisition of diffusionweighted images (DWI) is an alternative to the use of contrast agents, reducing the risk of nephrotoxicity, albeit without showing better performance than STIR imaging analyses [21,22] (2B).…”
Section: (2b)mentioning
confidence: 99%